2014
DOI: 10.1002/14651858.cd009447.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin versus unfractionated heparin for perioperative thromboprophylaxis in patients with cancer

Abstract: Low molecular weight heparin versus unfractionated heparin for perioperative thromboprophylaxis in patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…In a 2014 meta-analysis of 16 RCTs, of which 13 compared LMWH to UFH, two studies compared fondaparinux vs. heparin, and one compared dalteparin to tinzaparin. Eleven studies confirmed a statistically significant reduction in mortality in the 3-month follow-up period in favor of LMWH in relation to UFH (RR 0.71; 95% CI: 0.52-0.98) [66]. There was no difference in recurrence of thrombosis between LMWH and UFH used as initial treatment (RR 0.78; 95% CI: 0.29-2.08).…”
Section: Initial (5-21 Days) and Primary (3-6 Months) Treatment Of Vtementioning
confidence: 90%
See 1 more Smart Citation
“…In a 2014 meta-analysis of 16 RCTs, of which 13 compared LMWH to UFH, two studies compared fondaparinux vs. heparin, and one compared dalteparin to tinzaparin. Eleven studies confirmed a statistically significant reduction in mortality in the 3-month follow-up period in favor of LMWH in relation to UFH (RR 0.71; 95% CI: 0.52-0.98) [66]. There was no difference in recurrence of thrombosis between LMWH and UFH used as initial treatment (RR 0.78; 95% CI: 0.29-2.08).…”
Section: Initial (5-21 Days) and Primary (3-6 Months) Treatment Of Vtementioning
confidence: 90%
“…The effectiveness of low doses of unfractionated heparin (LDUH) in the prophylaxis of VTE in high-risk surgical patients has been well documented. However, in everyday clinical practice, for various reasons, this method of prophylaxis is less and less important compared with the use of LMWH; and it should be noted that both methods show high and comparable effectiveness [55][56][57][58][59][60][61][62][63][64][65][66].…”
Section: Recommendation 28mentioning
confidence: 99%
“…The benefits of UFH and LMWH remain to be properly studied in relation to flaps, but there does not seem to be increased complications with preoperative anti-coagulation. 50,51 However, preoperative thromboprophylaxis may provide ancillary benefits such as reducing the rates of VTEs after microsurgery. Bertolaccini et al 52 investigated the pharmacodynamics of fixed-dosed intra-operative UFH (500 U/h) and discovered that it did not reach therapeutic levels to prevent VTEs.…”
Section: Preoperative Managementmentioning
confidence: 99%
“…We have used this approach in several recently published Cochrane and non-Cochrane reviews [22][23][24][25][26][27][28][29][30][31][32] . One of these studies assessed probiotics for the prevention of Clostridium difficile infection (CDI) 28 .…”
Section: Illustrative Examplesmentioning
confidence: 99%